Efectos de la fertilización en la fase inicial de una plantación de Schizolobium parahyba (Vell.) S.F. Blake (pachaco) en el sector La Azucena del cantón Pichincha, provincia de Manabí - Espinales Chiguano, María Fernanda (2021)
The use of fertilizers in a particular soil is of vital importance for a quality production, in this way the raw material from this forest species will be used to the maximum. Considering the above, the main objective of the present investigation was to evaluate the effect of fertilizers on the growth, in the initial phase, of five-month-old Schizolobium parahyba (pachaco). The test was carried out in the La Azucena sector of the Pichincha canton belonging to the province of Manabí. A completely randomized design (DCA) was used, 4 treatments and 3 repetitions were carried out, a control without application and three types of fertilizers with doses of 60 g for each treatment, later we proceeded to take measurements of height and diameter of the shaft, the same one that was carried out every 15 days and there were a total of 5 intakes. The results obtained from the experimental design with the application of Sumicoat, NPK and Novatec fertilizers, have shown variability with respect to the height of the treatments in relation to the control (T0), because favorable results were obtained in the T2 treatment corresponding to the application of 60 g of NPK where it presented the best average with 75.41 cm, the T3 60 g treatment of Novatec obtained the second best average with 70.40 cm, while the lowest average was obtained by the T0 treatment without application of fertilizers ( Control) with 64.85 cm. Regarding the variable diameter of the stem of the pachaco, it was possible to observe among the evaluated treatments, the treatment T3 corresponding to 60 g of Novatec, obtained the highest average with 10.52 mm in diameter, on the other hand, the treatment T1 60g Sumicoat had 10.31 mm in relation to the diameter, while the T0 without fertilizer application (Control) with 9.56 mm. For the variable number of leaves, treatment T2 60 g of NPK, obtained the highest average with 3.33, on the other hand, treatment T0 without application of fertilizers (Control) 2.30, while T1 60 g of Sumicoat and T3 60 g from Novatec averaged 2.0 respectively. With the data obtained, it was established that the Novatec fertilizer is of high cost due to its high quality index, unlike the rest of fertilizers according to the economic analysis. Keywords: Fertilizers, plants, forest species, initial phase, growth.